A new method for the study of processes at the liquid-liquid interface using an array of microdroplets on a au electrode. - Simm, A; Chevallier, F; Ordeig, O; del Campo, F; Munoz, F; Compton, R (2006)
We report the fabrication of partially blocked gold electrodes, with regularly and hexagonally spaced inert hydrophobic blocks on their surface. The hydrophobic blocks, with diameters of 5 mum, are used to support liquid 5-nonyl-salicylaldoxime (Acorga-P50) droplets on the surface. By voltametrically monitoring the transport-controlled reduction rate of Cu(II) (in pH 5 solution) at the unblocked part of the gold surface it is possible to deduce, via simulation, the parameters controlling the rate of uptake of Cu(II) at the droplet-aqueous solution interface as the droplet "fills up" with Cu(II). Experimentally, it is recorded that the reduction current increases until the droplet is filled completely; after this, there is no further noticeable effect of the droplet coating. A rigorous theoretical analysis of the transients permits the deduction of partition coefficients between the aqueous solution and the organic-droplet phase and of diffusion coefficients within the droplet. The partition coefficient for Cu(II) between water and 5-nonyl-salicylaldoxime was found to be 200 at 25 degrees C and the diffusion coefficient of Cu(II) inside the organic phase was determined to be 5 x 10(-11) cm2 s(-1).